Trends of Diarrhoeal Diseases among Children under Five at the Princess Marie Louise Children`S Hospital: 2011-2014 - Owusu, B. (University of Ghana, 2017)
Introduction: In 2015, despite the availability of simple effective treatment, diarrhoeal diseases were noted as the leading killer of children accounting for 9 per cent of all deaths among children under age five worldwide. In Ghana, diarrhoeal diseases kill 14,000 children annually even though prevention and management is still available and accessible. The study was undertaken to assess the trends of diarrhoeal diseases among children under five years of age. Methods: A review of secondary data of children under five years of age who attended Princess Marie Louise Children’s Hospital from 2011-2014 and were diagnosed with diarrhoea was done. The data were exported from Microsoft excel 2010 to STATA 14 and analyzed by time, place and person. Frequencies and percentages were computed to describe the distribution of diarrhoea cases among the various age categories and place of residence. Time series analysis were used to evaluate the trend of diarrhoeal cases among children under five years of age. Results: A total of 2081 diarrhoeal cases were reported to the hospital from January, 2011 to December, 2014. Out of this majority were males 1,254 (60.3%). The trend of diarrhoeal diseases showed periodic pattern with three peaks observed for each year. The highest peak occurred from January to March. Diarrhoeal diseases prevalence for the period (2011-2014) was 10.52% (2081/19782) and decreased by 60.46% from 17.28% in 2011 to 7.90% in 2014, within the same period fatality also declined by 78.57% from 1.53% in 2011 to 0.83% in 2014. Male children aged 1-4 years and males were more predispose to diarrhoeal disease. In addition, children residing within Accra Metropolis were more prone to diarrhoeal diseases. Conclusion: The study found that during the study period, case fatality for diarrhoeal diseases declined from 10.14% in 2011 to 1.90 in 2014. The reasons for the decline included introduction of rotavirus vaccine, improvement in water supply, improvement in health promotion regarding safe water, etc. Majority of the children who reported to the hospital with diarrhoeal diseases were located within Accra Metropolis.
Thesis (MPH)
Keywords: Diarrhoeal; Diseases; Children; Princess Marie Louise Children`s Hospital